Organizational factors contribute to safety behaviour among malaysian firefighters in northern peninsular of Malaysia - Marimuthu, Vijayan (2021)
Fire and Rescue Department Malaysia is one of the highest and trusted emergency department in the country delivering fire and rescue, medical and humanitarian services. As community safety is a main concern in the department mission, the safety of firefighters is indispensable as well. This study explored the relationship between safety management practices and perceived threat of workplace accidents with safety behaviour. Questionnaires were used for data collection and data was analyzed using Statistical Package of Social Science (SPSS). A total of 325 respondents participated involving senior firefighters (KB 22) and firefighters (KB 19) from Northern States of Perlis, Kedah, Penang and Perak. Based on the analysis, it was found that safety training and safety rules and procedure were positively related to safety behaviour whereas other variables showed nonsignificant impact on safety behaviour. The discoveries hope to set a direction on important factors that cultivate fundamental safe practices to fire and rescue as well as emergency response related organizations policy makers.